Methodology of Data Collection in Information System (IS) - Kilani , Mohamed Al; Kobziev , Volodymyr (Current Overview on Science and Technology Research Vol. 9, 2022)
This chapter aims to give and clarify the components of research methodology in information system (IS), and compare between qualitative approach and quantitative approach, as well as justification for use of the case study in information system (IS). Research methodology in a research study is considered as an important element, and therefore determining the method of research methodology is very important step. The qualitative approach method provides explanations to explore a particular phenomenon, theory building and capturing everyday life through data collection and analysis. Research methodology is useful to establishing the structure of research, such as strategy, approach, research philosophy, and components of the methodology. The main features that distinguish the experimental study from other methods are the possibility of controlling the experimental variable or the cause to achieve the hypothesis. The goal of research design is to provide a clear picture of the structure of the research as well as the methods used, such as data collection, research questions, and data sources. The research design allows the researcher to outline all necessary methods and tools for the research, such as project theory and research methodology.